Treatment of vibro harveyi-infected peneaus monodon using alibutbut (Tabernaemontana pandacaqui Poir) plant powder. - Bacaling, Marivic Tabalina (2005.)
The cytotoxicity test of crude methanolic leaf extract using Brine Shrimp Lethality Asssay revealed that Alibutbut (Tabernaemontana pandacaqui Poir.) is safe to use in treating vibrio-infected penaeid shrimps., The effectiveness of the alibutbut powder against vibriosis was examined through the determination of the post-larvae 20 (PL 20) penaeid shrimp mortality and the water microbial assay after 48 hours. Percent penaied shrimp mortality (0-6.67 percent) and microbial count (2.91 x 10 raise to the 4th power - 3.26 x 10 raise to the 4th power cfu/mL) of the plant treatments were significantly lower compared to the negative control (no treatment) that exhibited 50 percent penaeid shrimp mortality and a microbial count greater than 6.00 x 10 raise to the 4th power cfu/mL. NThe results of the experiment showed that Alibutbut palnt powder is indeed effective in controlling Vibrio harveyi bacteria.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Alibutbut; Penaeus monodon -- Infected; Tabernaemontana pandacaqui Poir